Management of thoracic spine pain and dysfunction: A survey of clinical practice in the UK. (February 2019) - Heneghan, Nicola R.; Gormley, S.; Hallam, C.; Rushton, Alison
Abstract: Background: The thoracic spine (TS) is relatively under-researched compared to the neck and low back. As the challenge of managing spinal pain persists, understanding current physiotherapy clinical practice for TS pain and dysfunction is necessary to inform future research in this area. Objective: To investigate physiotherapy practice for managing thoracic spine pain and dysfunction (TSPD) in the UK, with a secondary focus on examining differences across settings and expertise. Design and method: A cross sectional e-survey informed by existing evidence was designed. Comprising closed and open questions, the survey is reported in line with Checklist for Reporting Results of Internet E-Surveys. Eligible participants were UK-trained physiotherapists managing patients with TSPD, recruited for 9 weeks up to 8/2/16. Data analysis included descriptive analyses (closed questions) and thematic analysis (open questions). Results: From the 485 respondents, fulfilling the required sample size, key findings included. Examination: Active motion testing, palpation and postural assessment was 'always' undertaken by >89% of respondents. Management: Active (exercises) and passive (e.g. mobilisations) techniques were used by >85% of respondents, with ∼50% using manipulation, taping and acupuncture. Practice settings: Although broadly similar passive techniques were used more in private practice and sport. Expertise: Broadly similar patterns were seen for use of exercise across levels of expertise, although differences observed for electrotherapy and manipulation. Conclusion: Despite limited research exercise is widely used in all areas of practice and across all level of expertise. Further research is required to investigate exercise prescription for TSPD and implementation of evidence-based practice. Highlights: Each week 4 patients are seen with TSPD compared to 12 lumbar and 8 cervical. Thoracic spine examination is included in neck, low back and shoulder complaints. Exercise is widely used for TSPD despite a paucity of supporting evidence. Passive hands on interventions are used more in private practice and sport settings. Use of electrotherapy and manipulation varied across levels of expertise.